Produção de mudas de mírtilo através de estacas lenhosas, semilenhosas e miniestacas - Fischer, Doralice Lobato de Oliveira (2007)
Blueberry cultivation is very recent in Brazil. The area expansion of this production is limited by the lack of quality seedlings The purpose of this research was to increase the amount of blueberry seedlings by developing and adapting propagation techniques economically feasible. Furthermore, to verify the effect of IBA (indolbutyric acid) on rooting of both hardwood and semi-hardwood cuttings, and the leaf area on rooting of mini-cuttings. This project was consisted of 3 experiments with different assessments: 1) the influence of 5 IBA concentrations (0, 1000, 2000, 4000 and 8000 mg L-1) on rooting of hardwood cuttings of 5 blueberry cultivars: Delite, Powderblue, Bluebelle, Clímax and Woodard; 2) the effect of different IBA concentrations (0, 1000, 2000 and 4000 mg L-1) on rooting of semi-hardwood cuttings of 2 blueberry cultivars: Delite and Bluebelle; 3) the rooting of blueberry mini-cuttings (cultivar Powderblue) under four treatments (T1 two leaves; T2 one leaf; T3 two leaves cut in half; T4 one leaf cut in half). All the experiments were set in a greenhouse equipped with intermittent micro-sprinkler system. After rooting phase, in 96% of treatments with hardwood cuttings the rooting rating, independent of cultivar, was higher to 55%. For semi-hardwood cuttings, Delite showed a rooting average percent of 88.25%, independent of the IBA presence. In regards to mini-cuttings, the one entire leaf treatment provided 96% of seedlings formed in 90 days.